2017
DOI: 10.3389/fnins.2017.00603
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Antiapoptotic Effects of Delta-Opioid Peptide [D-Ala2, D-Leu5] Enkephalin on Spinal Cord Ischemia-Reperfusion Injury in Rabbits

Abstract: Background: In our previous study, we found that regional administration of delta-opioid peptide [D-Ala2, D-Leu5] enkephalin (DADLE) could provide dose-dependent protection on spinal cord ischemia-reperfusion (I/R) injury in rabbits. However, the relative protective molecular mechanisms underlying this neuroprotection remain unclear. The purpose of this study was to investigate whether DADLE provided the protection in spinal cord I/R injury through its antioxidant property by decreasing malondialdehyde (MDA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…The precise molecular mechanisms responsible for the detrimental effects of SCII remain elusive; however, it is generally accepted that the SCII-induced locomotor deficits and tissue damage are in part attributable to the elevated oxidative stress, apoptotic signaling, as well as neuroinflammation that take place following SCII [6-9]. To date, there still lacks effective treatment for SCII, but alternative approaches exist that can protect against SCII through anti-inflammatory, antioxidative, or antiapoptotic activities [10, 11, 25]. In the current paper, we presented evidence that lycopene, a natural compound in tomato and many other red fruits and vegetables, improved SCII-induced neurological disabilities and suppressed neuroinflammation, thereby exerting neuroprotective functions.…”
Section: Discussionmentioning
confidence: 99%
“…The precise molecular mechanisms responsible for the detrimental effects of SCII remain elusive; however, it is generally accepted that the SCII-induced locomotor deficits and tissue damage are in part attributable to the elevated oxidative stress, apoptotic signaling, as well as neuroinflammation that take place following SCII [6-9]. To date, there still lacks effective treatment for SCII, but alternative approaches exist that can protect against SCII through anti-inflammatory, antioxidative, or antiapoptotic activities [10, 11, 25]. In the current paper, we presented evidence that lycopene, a natural compound in tomato and many other red fruits and vegetables, improved SCII-induced neurological disabilities and suppressed neuroinflammation, thereby exerting neuroprotective functions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the neuroprotective effects of DOR have received increasing attention. Pharmacological studies found that DOR activation by DADLE significantly promoted neuronal survival in multiple animal models 15,26 28 . Studies in cultured neurons suggested that DOR-mediated neuroprotection was associated with ionic homeostasis, cellular transcription, antioxidative stress, and antiapoptosis 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was collected and protein concentration was determined using a BCA protein assay kit (Beyotime, Shanghai, China). Superoxide dismutase (SOD), GSH, and GSSG levels were measured using a SOD, GSH, and GSSG Assay Kit (Nanjing Jiancheng Bioengineering Institute, Nanjing, China), performed according to the manufacturer’s instruction ( 24 ).…”
Section: Methodsmentioning
confidence: 99%